2022
DOI: 10.3390/machines10050334
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Fiber Scale Precision Dicing of Aramid Fiber-Reinforced Plastic Composites

Abstract: Aramid fiber-reinforced plastic (AFRP) composites are widely used in aerospace, rail transit, marine and military industries, due to their high specific strength, high impact resistance, fatigue resistance and excellent designable properties. In order to meet different application requirements, cutting processes need to be carried out, such as window opening, edge cutting and slit cutting. However, the characteristics of high tensile strength and toughness, low interlaminar strength, non-uniformity and anisotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Especially feed rate was found to have a significant effect on surface roughness. 40 Optimization of cutting parameters is necessary to reduce delamination, cutting forces and surface roughness values. One study showed that feed rate has a greater effect on the surface roughness of the drilled hole than cutting speed.…”
Section: Evaluation Of Surface Roughnessmentioning
confidence: 99%
“…Especially feed rate was found to have a significant effect on surface roughness. 40 Optimization of cutting parameters is necessary to reduce delamination, cutting forces and surface roughness values. One study showed that feed rate has a greater effect on the surface roughness of the drilled hole than cutting speed.…”
Section: Evaluation Of Surface Roughnessmentioning
confidence: 99%
“…These properties empower engineers to fine-tune aircraft component performance, adapting to the dynamic demands of the industry. This pairing imbues AFRP laminates with a potent combination of strength, lightweight nature, and resistance to high temperatures [5]. Aramid fibers contribute to structural strength and rigidity, while the polymer matrix offers adhesion and toughness [6].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al 2 conducted cutting test research on CFRP and found that the fiber orientation angle was u = 0°, u = 45°, and u = 90°, the hole wall quality is good, at u = 135°, the hole wall quality is poor. Wen et al 3 Milled AFRP at a sub-fiber scale with an ultra-thin diamond cutter. The results show that the surface quality is the best when the cutting speed is 91.11 m/s, the cutting depth is 0.2 mm, and the feed speed is 5 mm/s.…”
Section: Introductionmentioning
confidence: 99%